2014
DOI: 10.1002/hep.27140
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of autophagy during liver regeneration impairs energy charge and hepatocyte senescence in mice

Abstract: Autophagy is a homeostatic mechanism that regulates protein and organelle turnover and uses the amino acids from degraded proteins to produce adenosine 5'-triphosphate (ATP). We investigated the activity of autophagy-associated pathways in liver regeneration after partial hepatectomy (PHx) in liver-specific autophagy-related gene 5 (Atg5) knockout (KO) mice. Liver regeneration was severely impaired by 70% PHx, with a reduction in postoperative mitosis, but a compensating increase in hepatocyte size. PHx induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(116 citation statements)
references
References 42 publications
6
105
1
1
Order By: Relevance
“…Ding et al also found that the inhibition of autophagy with CQ or siRNA significantly promoted hepatocyte apoptosis in an ethanolinduced model [28]. Toshima et al found that autophagic activity was increased in mice after partial hepatectomy (PHx), and the DNA synthesis and cell proliferation were impaired in Atg5 KO mice after PHx [24]. In our study, we found that ALR suppressed hepatocyte apoptosis but the inhibition of autophagy reversed the anti-apoptosis effect of ALR.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Ding et al also found that the inhibition of autophagy with CQ or siRNA significantly promoted hepatocyte apoptosis in an ethanolinduced model [28]. Toshima et al found that autophagic activity was increased in mice after partial hepatectomy (PHx), and the DNA synthesis and cell proliferation were impaired in Atg5 KO mice after PHx [24]. In our study, we found that ALR suppressed hepatocyte apoptosis but the inhibition of autophagy reversed the anti-apoptosis effect of ALR.…”
Section: Discussionsupporting
confidence: 63%
“…Peng et al found that HGF increased LC3II conversion in primary mouse nonparenchymal cells (NPCs), and this effect was inhibited by an anti-HGF neutralization antibody [23]. Toshima et al found that HGF treatment increased LC3II levels in primary mouse hepatocytes [24]. These findings indicated that HGF promotes autophagy directly.…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis of the obtained data suggests that in 1 week after subtotal hepatectomy we observed two different stages of tissue regeneration. In rats of the reference group, the liver was still at the stage of active proliferation, growth, and differentiation requiring active mitochondrial respiration in complex bc1 [21] and enhanced production of ROS [22] inducing autophagy at the early stages of regeneration [18]. In experimental rats, the stage of active recovery of liver weight was apparently over and gave way to the stage of normalization of mitochondrial function; the rate of coupled respiration under these conditions decreased to normal by day 7.…”
Section: Resultsmentioning
confidence: 98%
“…Liver regeneration is impaired in old animals and in elderly humans (Schmucker & Sanchez, 2011; Takubo et al., 2000; Timchenko, 2009). Furthermore, a recent study demonstrated that autophagy plays a critical role in liver regeneration and may be essential for the preservation of cellular quality by preventing hepatocytes from becoming senescent and hypertrophic (Toshima et al., 2014). Importantly, Conboy et al.…”
Section: Discussionmentioning
confidence: 99%